The quadrupole moments of the deformed nuclei in the p-shel - Doma, S.B.; salman, Hasan; tfiha, amir darwish (Latakia University Journal -Basic Sciences Series, 2019)
The quadrupole moments of the deformed nuclei in the p-shell: 6Li, 7Li, 8Li, 9Be, 10B, 11B, 12C, and 14N are calculated as functions of the total spin I and the deformation parameter by assuming that these nuclei have axes of symmetry. Moreover, the single-particle wave functions of a nucleon in a deformed non-axially symmetric nuclei are used to calculate the matrix elements of the quadrupole moment operator. Accordingly, the quadrupole moments of the deformed nuclei in the p-shell 6Li, 7Li, 8Li, 9Be, 10B, 11B, 12C, and 14N are calculated as functions of the deformation parameter β, the non-axiality parameter γ, and the oscillator parameter , which is obtained as function of the mass number A. حسبت عزوم رباعيات الأقطاب الكهربائية للنوى المشوهة المتناظرة محورياً10B, 9Be, 8Li, 7Li, 6Li, C,11B, 12 و14N كتوابع للسبين الكلي I ومعامل التشوه β. إضافة إلى ذلك، استخدمت التوابع الموجية للجسيم المفرد (نكليون)طبقاً للنموذج الطبقي في النوى المشوهة وغير المتناظرة محورياً في حساب العناصر المصفوفية لمؤثر عزوم رباعيات الأقطاب الكهربائية وكذلك تم حساب عزوم رباعيات الأقطاب للنوى المشوهة التالية, 11B, 10B, 9Be, 8Li, 7Li, 6Li C12 و14N المشوهة والغير متناظرة محورياً في الطبقة pكتوابع لوسيط التشوه β ووسيط اللامحورية γ ووسيط الهزاز التوافقي ، والذي عبرنا عنه بدلالة العد د الكتلي A.